Pasteurised eggs - a food safety solution against Salmonella backed by sensorial analysis of dishes traditionally containing raw or undercooked eggs - Mihalache, Octavian Augustin (2022)
This study evaluates the potential of pasteurised eggs to be used as a replacement for raw eggs in recipes where eggs remain uncooked or undercooked. Sensory tests were performed by 178 untrained panellists (143 from Portugal and 35 from Romania) using a 9-point hedonic scale. The tested recipes were tiramisu, chocolate mousse, eggnog, hollandaise sauce, and condensed milk mousse (Baba de camelo). While in Portugal the colour and texture of the chocolate mousse prepared with pasteurised and unpasteurised eggs differed significantly, no significant differences in regards to the organoleptic attributes were recorded in Romania. Nonetheless, the results revealed comparable distribution scores regarding the overall acceptability for all the recipes indicating an agreement among panellists for both raw and pasteurised eggs dishes in both countries. The regression analysis showed that the main drivers of consumers’ acceptance of dishes made with pasteurised eggs are flavour and texture. This research demonstrates that five dishes prepared with liquid pasteurised eggs are accepted by consumers as they cannot clearly be distinguished from their counterparts prepared with raw eggs. As Salmonella-contaminated eggs are the most frequent cause of salmonellosis, pasteurised eggs can be used as a safer ingredient to substitute shell eggs in raw egg-based dishes without significant reduction of the sensory quality of the dish. Since liquid pasteurised eggs are already widely used, especially by industry and restaurants, we provide reasons supporting pasteurisation of eggs in shell as a more convenient solution for consumers. Pasteurised eggs, either liquid or in shell, constitute a way to reduce the burden of foodborne diseases by diminishing the number of cases of salmonellosis associated with cooking at home. Researchers and food safety authorities can use our results as a starting point for future studies or intervention strategies.